Social economy as a new challenge - Filek, Janina (Annales. Etyka w Życiu Gospodarczym, 2019)
The article discusses the concept of the social economy. In the first part, some essential historical sources of the subject matter are described. The second part deals with the concept of social economy, taking into special consideration its definitional problems, founding values and characteristic principles as well as the dilemmas and difficulties connected with its implementation.